Bibliometric analysis and visualization of literature on assisted reproduction technology - Meng, Fanchao; Deng, Sheng; Wang, Lu; Zhou, Yumei; Zhao, Mengjie; Li, Haibin; Liu, Dong; Gao, Guojing; Liao, Xiaoxing; Wang, Jisheng (Frontiers in Medicine, 2022)
Assisted reproductive technology (ART) is a method that uses various techniques to process sperm or eggs. Assisted reproductive technology involves removing eggs from a woman's ovaries, combining them with sperm in the laboratory, and returning them to the woman's body or donating them to another woman. In total, 6,288 articles on ART were published between 2001 and 2022 in 1,013 journals. Most of these published articles represent the global research status, potential hotspots and future research directions. Publications and citations of research on assisted reproductive technology have steadily increased over the past few decades. Academic institutions in Europe and the United States have been leading in assisted reproductive technology research. The countries, institutions, journals, and authors with the most published articles were the United States (1864), Harvard Univ (108), Fertility and Sterility (819), and Stern, Judy E. (64). The most commonly used keywords are Assisted reproductive technology (3303) and in-vitro Fertilization (2139), Ivf (1140), Pregnancy (1140), Women (769), Intracytoplasmic Sperm injection (644), In Fertilization (632), Risk (545), and Outcome (423). Presently, Frozen embryo transfer, Intracytoplasmic Sperm Injection, and Invitro fertilization are the main research topics and hotspots in the field of assisted reproductive technology.